Penzion Mikulov - Smolinský, Patrik (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Obsahem této diplomové práce je návrh novostavby penzionu s restaurací ve městě Mikulov. Jedná se o objekt s dvěma nadzemními podlažími a částečným podsklepením. V suterénu se nachází technická místnost a posilovna. V 1.NP se nachází recepce, restaurace se zázemím a pokoje pro ubytování. Jeden pokoj je navržen jako bezbariérový. Ve 2.NP se nachází pokoje pro ubytování, zázemí pro úklid a společenská místnost. Svislé nosné konstrukce jsou navrženy z keramického zdiva, v suterénu ze ztraceného bednění. Objekt bude zastřešen částečně plochou střechou, valbovou střechou a částečně vegetační střechou. Projektová dokumentace byla zhotovena dle platných právních a technických předpisů.

The content of this diploma thesis is the design of a new boarding house with restaurant in Mikulov. The building has 2 above – ground floors and a partial basement. In the basement is utility room and fitness room. In 1st floor there is reception, restaurant with facilities and rooms for accomodation. One room is designed as a berrier – free. In the 2nd floor there are rooms for accomodation, facilities for cleaning and common room. The vertical supporting structures are designed from clay masonry, in the basement of the concrete formwork. The building will be covered partly by flat roof, hip roof and partly by vegetation roof. The design documentation has been prepared according to valid legal and technical regulations.
Boarding House Mikulov
Keywords: Penzion; restaurace; dvě nadzemní podlaží; částečně podsklepený; keramické zdivo; ztracené bednění; plochá střecha; valbová střecha; vegetační střecha.; Boarding house; restaurant; two above – ground floors; partial basement; clay masonry; concrete formwork; flat roof; hip roof; vegetation roof.